An Exploratory Study of Endogenous Pain Modulatory Function in Patients Following Mild Traumatic Brain Injury. Issue 11 (2nd April 2019) - Carey, Christopher; Saxe, Jonathan; White, Fletcher A; Naugle, Kelly M
Abstract: Background. Recent animal research suggests that mild traumatic brain injury (mTBI) facilitates abnormal endogenous modulation of pain, potentially underlying the increased risk for persistent headaches following injury. However, no human studies have directly assessed the functioning of endogenous facilitory and inhibitory systems in the early stages after an mTBI. Objective. The purpose of this exploratory study was to examine trigeminal sensitization and endogenous pain inhibitory capacity in mTBI patients in the acute stage of injury compared with matched controls. We also examined whether post-traumatic headache pain intensity within the mTBI sample was related to sensitization and pain inhibitory capacity. Methods. Twenty-four mTBI patients recruited from emergency departments and 21 age-, race-, and sex-matched controls completed one experimental session. During this session, participants completed quantitative sensory tests measuring trigeminal sensitization (pressure pain thresholds and temporal summation of pain in the head) and endogenous pain inhibition (conditioned pain modulation). Participants also completed validated questionnaires measuring headache pain, depression, anxiety, and pain catastrophizing. Results. The results revealed that the mTBI group exhibited significantly decreased pressure pain thresholds of the head and decreased pain inhibition on the conditioned pain modulation test compared with the control group. Furthermore, correlational analysis showed that the measures of trigeminal sensitization and depression were significantly associated with headache pain intensity within the mTBI group. Conclusions. In conclusion, mTBI patients may be at risk for maladaptive changes to the functioning of endogenous pain modulatory systems following head injury that could increase risk for post-traumatic headaches.